Digital nudges to stimulate healthy and pro-environmental food choices in E-groceries. (1st May 2022) - De Bauw, Michiel; De La Revilla, Lucia Segovia; Poppe, Veerle; Matthys, Christophe; Vranken, Liesbet
Abstract: In response to the detrimental health- and environmental impacts of European consumers' dietary patterns, Nutri-Scores and Eco-Scores have been introduced on packages as guidance for choices. Whereas the scores are promising to improve food choices from a nutritional point of view, the scant available literature suggests very limited effects on the environmental impact of food choices. Therefore, there remains a need to explore ways to bring about improvements in both areas. As a growing share of consumers buys food groceries online, new opportunities to steer food choices are being created. This article explores the potential of several digital functionalities to further stimulate healthier and pro-environmental food choices amongst consumers. These functionalities included product recommendation agents, product scores, a real-time average impact score of the chosen food basket and a personalised social norm. Those were tested in a two-stage randomized controlled trial with 1000 Belgian household food decision makers in a mock-up E-grocery. Indices reflecting the nutritional quality (NQI) and environmental impact (EII) of the selected food baskets were calculated. The results indicate that at first, displaying a combined Nutri- and Eco-Score at product level led to improved NQI's, but not EII's. However, the scores also led to shifting behaviour in EII's when facilitated with recommendation agents. The display of the average impact scores of the selected basket and of social norms did not lead to additional improvements. Hence, a combined Nutri- and Eco-Score labelling system is recommended, but an enabling environment to consider both scores is important to realise a shift towards more healthy and environmentally friendly food choices. Apart from manifesting healthier and environmentally friendly products with a centralised labelling system, improving their accessibility should be considered at least as important for behavioural changes.